2005
DOI: 10.1103/physrevb.72.014451
|View full text |Cite
|
Sign up to set email alerts
|

Polar magneto-optical Kerr effect for low-symmetric ferromagnets

Abstract: The polar magneto-optical Kerr effect (MOKE) for low-symmetric ferromagnetic crystals is investigated theoretically based on first-principle calculations of optical conductivities and a transfer matrix approach for the electrodynamics part of the problem. Exact average magneto-optical properties of polycrystals are described, taking into account realistic models for the distribution of domain orientations. It is shown that for low-symmetric ferromagnetic single crystals the MOKE is determined by an interplay o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This contribution is completely independent of scatterers and is now often referred to as the intrinsic contribution to the anomalous Hall effect. The intrinsic anomalous Hall effect has been evaluated explicitly in recent years for a variety of different ferromagnetic materials using relativistic first principles electronic-structure methods 23,24,25 . It can be non-perturbative in character because of band crossings, a property that partially explains the fact that it is often quantitatively important.…”
Section: Application To the Ahementioning
confidence: 99%
“…This contribution is completely independent of scatterers and is now often referred to as the intrinsic contribution to the anomalous Hall effect. The intrinsic anomalous Hall effect has been evaluated explicitly in recent years for a variety of different ferromagnetic materials using relativistic first principles electronic-structure methods 23,24,25 . It can be non-perturbative in character because of band crossings, a property that partially explains the fact that it is often quantitatively important.…”
Section: Application To the Ahementioning
confidence: 99%
“…where "t" means the transpose of the conductivity tensor according to Onsager's relation. 67 σ xy as shown in eq 3 changes the sign under operation, thus implying that the Kerr angle is also inverted under operation according to eq 7. In the same way, it can be shown that the operation can also reverse the Kerr angle in the MPG 3 system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the other hand, under the scriptT symmetry operation, true σ̲ ̲ of MPG 3 transforms as follows: scriptT : true σ̲ ̲ scriptT true σ̲ ̲ scriptT 1 = true σ̲ ̲ normalt where “t” means the transpose of the conductivity tensor according to Onsager’s relation . σ xy as shown in eq changes the sign under scriptT operation, thus implying that the Kerr angle is also inverted under scriptT operation according to eq .…”
Section: Resultsmentioning
confidence: 99%
“…with respect to that of +θ system (invariant under M z and transpose by T according to Onsager's relation [65]). It leads to a fascinating property for the p3 case (RL-T2): the sign of ε xy (σ xy ) is changed, and, therefore, one can reverse the Kerr angle (i.e.…”
Section: Structures and Symmetriesmentioning
confidence: 99%